EFFICIENCY OF WATER AND CHROME USE IN CABRETTA SHEEP TANNING PROCESS USING EXHAUSTED TANNING CHROME METHOD - Akbar Izzulhaq; Mustafidah Udkhiyati; Wahyu Fajar Winata (Politek ATK Yogyakarta Press, 2022)
This study aims to make chromium and water more efficient in the tanning process. The methods used include water efficiency from 100% to 50% and chromium reduction from 6% to 4% using exhausted chrome tanning method. The raw material used is grade 6 pikel sheepskin and the auxiliary chemical used is acrylic copolymer. The tests carried out were organoleptic, physical and chromium content in the waste. Organoleptic and physical tests showed that the condition of slackness, and the suitability of color on the crust of the pearl white cabretta article had met consumer purchasing standards. In the results of physical testing of samples using the exhausted chrome tanning method, almost all of them meet the test standards from SII-0943-84. Waste testing showed that the use of the efficiency method had a significant decrease in the amount of total chromium, from 757.35 mg/L to 487.80 mg/L.